Urgence and Security of Digitalization of Land Electronic Certificate Issuance Documents - Nur Rohman (Universitas PGRI Madiun, 2022)
This study aims to determine the urgency and how to regulate personal data protection and security for the issuance of electronic land certificates. The author concludes first, that the regulation of personal data protection has been regulated through the 1945 Constitution of the Republic of Indonesia and other laws and regulations. However, there is no law that specifically regulates the protection of personal data. Currently the Personal Data Protection Bill has been included in the 2022 Prolegnas. Regarding the security of electronic land certificates, the Ministry of ATR/BPN RI has implemented several security measures, but the potential for personal data leakage still exists. Second, the policy for issuing electronic land certificates is currently not urgent to implement. This is based on the first, the lack of socialization of the policy to the public. Second, it is still prone to leaks of personal data. Third, there are still many unresolved agrarian conflicts, one of the causes of which is related to the overlapping of land ownership rights. So the author suggests first to immediately ratify the Personal Data Protection Bill so that the legal umbrella is clearer. Second, urging the government to immediately resolve existing agrarian conflicts and complete the land certification program first through PTSL